Spontaneous variability of Streptomyces glomeratus, a producer of the amthracycline antibiotics beromycins - Blumauerová, M; Podojil, M; Gauze, G F; Maksimova, T S; Panos, J; Vanĕk, Z (Folia microbiologica, 1980)
Spontaneous variants of the beromycin-producing strain Streptomyces glomeratus 3980 were divided into five groups (A-E) according to increasing antibiotic activity. The most active variants (group E) differed from the other types and the wild strain by a suppressed ability to produce aerial mycelium and melanoid piogment and by an increased production of propionic acid. Strains with a 12-fold higher antibiotic production capacity (with respect to strain 3980) were obtained by selection of superior segregants from submerged cultures of the E type.
Keywords: antracykliny; Genetic Variation; naftaceny; Pigments, Biological; Propionates; Anthracyclines; genetická variace; propionáty; Naphthacenes; Streptomyces; Antibiotics, Antineoplastic; protinádorová antibiotika; biologické pigmenty